Implementasi Algoritma Caesar Cipher dan Rivest Shamir Adleman Super Enkripsi Teks Pesan dengan Karakter Ascii - Fahrezi Kusuma, Andra; Agustini, Siti; Hakimah, Maftahatul; Kurniawan, Muchamad (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
Humans are never separated from information needs when viewed from technology use. Data security is important because it relates to confidentiality, integrity, authentication, and privacy. Some information has privacy that the public should not share. Therefore we need a way to secure information so that the information does not spread widely to unauthorized parties. This study used Caesar Cipher and RSA Algorithms to secure a text message. So the data would not be easily hacked by irresponsible parties. The encryption process started using the Caesar Cipher Algorithm by entering a key/shift of letters to produce a ciphertext. Ciphertext Caesar is used for the encryption process for the second time using the RSA algorithm. RSA ciphertext result was converted into ASCII characters. The algorithm proposed to secure message text data using a combination of letters and numbers in each trial. The Caesar Cipher Algorithm implementation results obtained an average avalanche effect value of 35.03%. At the same time, the RSA algorithm obtained an average avalanche effect value of 55.10%. And the Caesar-RSA algorithm obtained an average avalanche effect value of 59.015%. The best test results were obtained by combining the two algorithms, Caesar Cipher and RSA, which showed that the proposed algorithm could secure message text data effectively.